Improvement of thermal stability and luminescence in Ca6Ce2Na2(PO4)6F2:Mn2+/Tb3+via the substitution of Ca with Sr/Ba for structural modification. (1st February 2021) - Zhang, Li; Wang, Zhijun; Dai, Danjie; Xing, Zhenhua; Zhao, Jinxin; Li, Xiaotong; Liu, Chunjiao; Wang, Dawei; Yang, Zhiping; Li, Panlai
Abstract : A series of Ca6− x−y Sr x Ba y Ce2 Na2 (PO4 )6 F2 (CMCNPF, M = Sr 2+ /Ba 2+ ), CMCNPF:0.1Mn 2+ and CMCNPF:0.1Tb 3+ phosphors were synthesized by a high temperature solid-state method. Abstract : A series of Ca6− x − y Sr x Ba y Ce2 Na2 (PO4 )6 F2 (CMCNPF, M = Sr 2+ /Ba 2+ ), CMCNPF:0.1Mn 2+ and CMCNPF:0.1Tb 3+ phosphors were synthesized by a high temperature solid-state method. In order to improve the luminescence properties of the phosphors, Sr 2+ and Ba 2+, which are in the same main group as Ca 2+, are used to partially substitute Ca 2+ in the host. The excited state electrons of Ce 3+ and Mn 2+ are located in the outermost layer of the ions and are easily influenced by the external crystal field. Therefore, when substituted for cations, the emission peaks of Ce 3+ and Mn 2+ tend to shift, while that of Tb 3+ remains unchanged. For the peak shift of Ce 3+, this may be considered from the two aspects of nephelauxetic effect and crystal field splitting. However, the low-temperature spectra and lifetimes of the two emission peaks show that the shift of the Ce 3+ emission peak is only influenced by the Ca1 lattice. In addition, the blueshift of the luminescence center Mn 2+ is influenced by the average bond length of the polyhedron and the symmetry of the polyhedron. Regulating the composition of the cations can improve the symmetry of the polyhedron occupied by the luminescence center, increase the rigidity of the crystal structure, and improve the thermal stability of the luminescence center to a certain extent.